Primary Renal Carcinoid Tumor - Siamak Daneshmand; Shahin Chandrasoma; Shandra Wilson (The Scientific World Journal)
Primary carcinoid tumors originating in a normal kidney are exceptionally rare. We describe a case of a 52-year-old woman who presented with vague back pain and was found to have a 4-cm mass in the medial aspect of the left kidney. Radical nephrectomy and retroperitoneal lymphadenectomy were performed. Histopathology revealed a typical carcinoid tumor with 1 out of 17 lymph nodes involved. She has no evidence of recurrence or metastasis on 7-month follow-up.